The 2010 Outbreak of Cholera among Workers of a Jute Mill in Kolkata, West Bengal, India (Journal of Health, Population and Nutrition, 2011)
On 10 March 2010, an outbreak of diarrhoeal disease was reported among workers of a jute mill in Kolkata, West Bengal, India. The cluster was investigated to identify the agent(s) and the source of infection and make recommendations. A suspected case of cholera was defined as having >3 loose watery stools in a 24-hour period and searched for case-patients in the workers’ colony. The outbreak was described by time, place, and person, and a case-control study was conducted to identify the source of infection. Rectal swabs were collected from the hospitalized case-patients, and the local water-supply system was assessed. In total, 197 case-patients were identified among 5,910 residents of the workers’ colony (attack rate 3.33%). Fifteen of 24 stool samples were positive for Vibrio cholerae O1. The outbreak started on 7 March, peaked on 11 March, and ended on 16 March 2010. Compared to 120 controls, 60 cases did not differ in terms of age and socioeconomic status. Drinking-water from the reservoir within the mill premises was associated with an increased risk of illness [odds ratio: 26.7, 95% confidence interval (CI) 11.4-62.6) and accounted for most cases (population attributable risk percentage=82%, 95% CI 70.8-92.9). An outbreak of cholera occurred among workers of the jute mill due to contamination of the drinking-water reservoir. It occurred within a few days of re-opening of the mill after the workers’ strike. Health authorities need to enforce disinfection of drinking-water and regularly test its bacteriological quality, particularly before re-opening of the mill after the strike. Key words: Case-control studies; Disease outbreaks; Cholera; Vibrio cholerae; Water pollution; Water supply; India DOI: 10.3329/jhpn.v29i1.7561 J HEALTH POPUL NUTR 2011 Feb;29(1):9-13